Práctica de la ética en el desempeño profesional del contador público colegiado de la libertad - Arteaga Chigne, Victoria (2009)
The present descriptive - transectional research addressed the ethical behaviour of the public accountant La Libertad-Peru. We tried to demonstrate that is a low degree of the practice of ethics in the performance of the public accountant in La Libertad. We worked with a sample of 196 accountants. We used a simple design; the quantitative-qualitative method; 40 items a structured questionnaire, on its dimensions: the fundamental principles and general rules of the code of ethics; under reliable and valid statistics. Additionally, interviews were done to fourteen countable experts, and 24 resolutions of the Peruvian Fiscal Court, in which the accountant was involved, were examined. It was found that 87% of public accountants think the code of ethics is important, just 52% of them know it and 35% practice the core principles and general rules of the code of ethics at a satisfactory degree. Furthermore, the documents analysis and the interviews to senior professionals revealed that the characteristics that risk the behavior of the public accountant are: subordination to the employer, income levels, professional maturity, disloyal competition among accountants and ignorance of the code of ethics, all of which led us to conclude that there is a low degree of the practice of ethics in the performance of the public accountant in La Libertad. For this reason, the strengthening of professional competences, personal skills and ethics are necessary.